Lesson Study-Based Mathematics Learning Using Cooperative Model on Single Interest and Compound Interest Materials - Latifah, Roykhana; Suparni; Prasetyo, Aris Budi (Pusat Studi Pengembangan Pembelajaran Matematika, 2024)
The implementation of lesson study-based mathematics learning with cooperative model at Colombo High School showed positive results in improving students' engagement and understanding of single and compound interest material. This study aims to explore the effectiveness of the cooperative learning model, particularly through two cycles of lesson study. The method used was a case study with data collection through observation, interviews, and observation sheets. In the first cycle, using the Think Pair Share (TPS) model, it succeeded in making student participation active although there were still challenges such as lack of focus. To overcome this problem, the second cycle applied the Team Games Tournament (TGT) model, which proved more effective in increasing student enthusiasm and engagement. The reflection results showed the need for improvement in group division to be more heterogeneous and increase students' problem-solving literacy. Continuous evaluation through discussions between model teachers and subject teachers is essential to identify and improve strengths and weaknesses in the implementation of learning. The implication of this research shows that the implementation of lesson study can be an effective strategy to improve the quality of mathematics learning in secondary schools.